The thin book of trust an essential primer for building trust at work - Feltman, Charles (Berrett-Koehler Publishers, Inc., 2024)
"Feltman's phenomenal bestseller with almost 100,000 copies sold across two editions outlines in a very simple and quick way the art of building trust between people in organizations as a core essential workplace competency. Trust is not something that happens naturally but is a skill that must be developed and practiced in order to be effective. But unlike the many skills that are merely nice to have, the ability to operate and move with trust is the most important of all, as no leader or organization can move forward without trust at the heart of its operational processes"--